Risk of incident dementia in late-life depression treated with antidepressants: A nationwide population cohort study. (October 2020) - Su, Jian-An; Chang, Chih-Cheng; Yang, Yao-Hsu; Chen, Ko-Jung; Li, Yueh-Ping; Lin, Chung-Ying
Background: Antidepressants are frequently used to treat depression in patients with dementia. In addition, late-life depression is associated with the incidence of subsequent cognitive impairment or dementia. However, the association between exposure to antidepressants in late-life depression and the development of incident dementia remains understudied. Methods: Through a population-based retrospective cohort design, data were extracted from the Taiwan National Health Insurance Research Dataset of medical claims registered from 1998–2013. We collected data of individuals who had received a new diagnosis of depression between 2000 and 2007. We excluded those who received a diagnosis of depression and were given antidepressants before 2000 and those younger than 60 years. The primary outcome was the occurrence of incident dementia. The time from the prescription of antidepressants or the diagnosis of depression until the outcome or the end of 2013 was calculated as the time to event. A total of 563, 918 cases were included and were divided into either antidepressant users or antidepressant nonusers. Cox proportional hazards models were used to calculate the hazard ratio and 95% confidence interval. Results: Exposure to antidepressants did not increase the risk of dementia in patients with late-life depression at either a low exposure dosage (hazard ratio: 1.06, 95% confidence interval: 0.91–1.23) or a high exposure dosage (hazard ratio: 1.07, 95% confidence interval: 0.95–1.20). To confirm the validity of our results, we performed a sensitivity analysis and subgroup analysis, and the post-hoc results were consistent with the main results. Conclusion: Antidepressants did not increase the risk of incident dementia in patients with late-life depression.